(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Several second order lowstand wedges are recognized in the Jurassic-Early Cretaceous sedimentary record of the backarc Neuquén Basin (central-west Argentina). They are distinguished by sharp based continental and marginal marine siliciclastic deposits encased in offshore shales. The Kimmeridgian lowstand wedge was developed slightly after the emergence of the Andean magmatic arc and the tectonic inversion of previous intrabasinal extensional structures. As a result, the Neuquén Basin was compartmentalized into three main depocentres characterised by widespread continental sedimentation under arid to semiarid climatic conditions. A fluvial-dominated system characterised by systematic downstream changes in architectural style is recognized in the Northwestern Depocentre. A gravely and sandy bedload fluvial system was developed in the southern upstream sector, while ticker beds of finer-grained sediments formed in a distal ephemeral fluvial system prevail in the downstream part of the system. The overall fining upward stacking pattern of the sedimentary record in the Northwestern Depocentre accompanied by frequent development of soil horizons and darker deposits suggests a change towards higher accommodation and high water table emplacement. In the Southwestern and Eastern Depocentres, the sedimentary successions show a conspicuous internal transition from fluvial ephemeral fluvial systems to aeolian systems. However, the lowstand deposits of the Eastern Depocentre are characterised by a larger areal distribution and a thicker record of both the fluvial and the aeolian deposits. Marked changes in thickness and in the depositional style of the fluvial and aeolian facies associations within the Southwestern and Eastern depocentres indicate that the sedimentary infill was controlled by systematic variations in accommodation. Low accommodation conditions favoured a high degree of lateral migration of fluvial channels with substantial erosion of fine-grained deposits and the development of sinuous-crested aeolian dunes typically associated with wet interdune deposits. Under higher accommodation conditions the fluvial deposits show a retrogradational stacking with preservation of thick packages of fine-grained sediments, while a large sand sea characterised by amalgamation of dune deposits was developed in the aeolian-dominated uppermost successions. The detailed analysis of the Kimmeridgian lowstand wedge of the Neuquén Basin illustrates how facies and stratigraphic organisation responded to regional and temporal changes in basin configuration, accommodation, sediment supply and water table position. The Kimmeridgian lowstand deposits are geographically distributed as the subsequent transgressive deposits and reveal no major basinward shift during the early stages of sequence stacking. However, they show a much more complicated facies distribution. Consequently, the lowstand wedge deposits better reflect the complex interplay of episodic local tectonism, siliciclastic source area variation and climatic change.